Obesity’s Influence on the Psychosocial Wellbeing of Primary School Students in Kota Kinabalu: A Phenomenological Approach - D. Maryama Ag Daud; Christina Peter Ligadu; Farijah Ismail (Human Resource Management Academic Research Society (HRMARS), 2021)
Overweight and obesity among youngsters have grown quickly worldwide in recent decades, including in Malaysia. The major goals of this study are to investigate the psychological impacts that obesity has on children and to find out the quality of life of obese children. A qualitative study design and a phenomenological approach are used in this study. The study used a purposive sampling method. A sample was selected of five obese male and female students aged 11 and 12 years. The selected students attend a government primary school in the city of Kota Kinabalu, Sabah, Malaysia. The data collection process was done using the methods of interviews, observations, and document analysis. Based on the findings of the study, there are three emerging themes that explain the psychological effects experienced by primary school students that impact their quality of life. These include: (a) social health, (b) mental health, and (c) physical health complications. In conclusion, this study found that obesity causes an enormous number of psychosocial problems with regard to the personal and social lives of children. Second, this research informed parents about the prevalence of bullying in the home, perpetrated by siblings. Finally, these findings contribute to the growing body of research revealing the harmful effects of weight-related stigma, even at a young age, and may be valuable in modifying public policy about weight discrimination.